Prioritization of Companion Animal Transmissible Diseases for Policy Intervention in Europe. (July 2016) - Cito, F.; Rijks, J.; Rantsios, A.T.; Cunningham, A.A.; Baneth, G.; Guardabassi, L.; Kuiken, T.; Giovannini, A.
Summary: A number of papers have been published on the prioritization of transmissible diseases in farm animals and wildlife, based either on semiquantitative or truly quantitative methods, but there is no published literature on the prioritization of transmissible diseases in companion animals. In this study, available epidemiological data for diseases transmissible from companion animals to man were analysed with the aim of developing a procedure suitable for their prioritization within a European framework. A new method and its associated questionnaire and scoring system were designed based on methods described by the World Organisation for Animal Health (OIE). Modifications were applied to allow for the paucity of specific information on companion animal transmissible diseases. The OIE method was also adapted to the subject and to the regional scope of the interprofessional network addressing zoonotic diseases transmitted via companion animals in Europe: the Companion Animals multisectoriaL interprofessionaL Interdisciplinary Strategic Think tank On zoonoses (CALLISTO). Adaptations were made based on information collected from expert groups on viral, bacterial and parasitic diseases using a structured questionnaire, in which all questions were closed-ended. The expert groups were asked to select the most appropriate answer for each question taking into account the relevance and reliability of the data available in the scientific literature. Subsequently, the scoring of the answers obtained for each disease covered by the questionnaire was analysed to obtain two final overall scores, one for human health impact and one for agricultural economic impact. The adapted method was then applied to select the 15 most important pathogens (five for each pathogen group: viral, bacterial and parasitic) on the basis of their overall impact on public health and agriculture. The result of the prioritization exercise was a joint priority list (available atwww.callistoproject.eu ) of relevant pathogens according to these two criteria. As the scope of CALLISTO was comprehensive in terms of geographical area, animal species involved and impact of the diseases, the list of prioritized diseases had to accommodate the realities in different European countries and the differences in biology and animal–human relationships in a wide range of species including cats and dogs, pet pigs and sheep as well as captive reptiles. The methodology presented in this paper can be used to generate accurate priority lists according to narrower and more specific objectives.